2015
DOI: 10.3109/13685538.2015.1105796
|View full text |Cite
|
Sign up to set email alerts
|

Association of low serum 25-hydroxyvitamin D levels with the frailty syndrome in Mexican community-dwelling elderly

Abstract: These results suggest that older adults with low 25(OH)-vitamin D levels are associated with the probability to being frail compared with those with sufficient vitamin D levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…14 This result is of concern, if we consider that a high inadequacy was also observed in calcium intake and that the lack of both of these nutrients predisposes this population to a greater risk of osteoporosis, frailty, 29 falls, 30 fractures, 31,32 functional dependency 33 and loss of muscle function. 34 In a random sample of 158 Mexican OA of the 2006 Ensanut, 33% had suboptimal concentrations of vitamin D. 35 This problem has been recently documented in Latin America.…”
Section: Discussionmentioning
confidence: 99%
“…14 This result is of concern, if we consider that a high inadequacy was also observed in calcium intake and that the lack of both of these nutrients predisposes this population to a greater risk of osteoporosis, frailty, 29 falls, 30 fractures, 31,32 functional dependency 33 and loss of muscle function. 34 In a random sample of 158 Mexican OA of the 2006 Ensanut, 33% had suboptimal concentrations of vitamin D. 35 This problem has been recently documented in Latin America.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the Toledo Study for Healthy Aging (n=592) reported that low serum 25OHD was associated with frailty (OR 1.65 95% CI 1.02-2.67, p=0.04), defined using the phenotype model(19). These findings were supported by an analysis of the European Male Ageing Study (n=1504) (88), a Mexican study of over 70s (n=331)(89), and a large Austrian study (n=940)(90), which also observed significant associations between low serum 25OHDand individual components of frailty including physical exhaustion, inactivity and reduced gait speed. A smaller Taiwanese study (n=215), reported a strong association between vitamin D status and frailty (odds ratio, OR, 10.CI 2.6 to 44.3) (91).…”
mentioning
confidence: 88%
“…[ 8 ] In regard to the elderly, a direct association between low 25(OH)D levels and frailty syndrome has recently been reported. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…[8] In regard to the elderly, a direct association between low 25(OH)D levels and frailty syndrome has recently been reported. [9] It is worth mentioning, here, that VD also has noncalcemic and nonskeletal effects. Several studies have reported an inverse association between VD levels and the risk of oral, gastrointestinal, urinary, ocular, and respiratory infections.…”
mentioning
confidence: 95%